Ritual memories on the Napo River. The rubber trade and the napuruna in northeastern Peru. - Pino, Nehemias (2022)
This article reflects on the memory of the rubber boom in the mid Napo River towards the end of the XIX century and the beginning of XX century in the village of Angoteros. In this article, we develop a theoretical discussion to better understand a complex memory through the notion of phenomenological texts and perspectivism. In the ethnographic data, we present the image of the yakuruna boat, generated in ayahuasca rituals, as a text that accounts for the relationship of the people of Angoteros with the commercial dynamics along the rubber trade. We aim that the symbolic complex of the master spirits and the yakuruna boat start from a phenomenological text that defines the memories of the Rubber Boom in the mid Napo River region.